2016
DOI: 10.20471/acc.2016.55.03.03
|View full text |Cite
|
Sign up to set email alerts
|

Ventilator-Associated Pneumonia: Comparing Cadaveric Liver Transplant and Non-Transplant Surgical Patients

Abstract: SUMMARY -Ventilator-associated pneumonia is a frequent complication in intensive care surgical patients, particularly those with high severity scores on admission. We studied the incidence and clinical outcome of ventilator-associated pneumonia among patients undergoing major general surgery procedures and those undergoing cadaveric liver transplantation in our hospital. Patients with the intensive care unit stay longer than four days having undergone surgery or transplantation and mechanically ventilated for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 33 publications
(35 reference statements)
0
1
0
Order By: Relevance
“…Similar findings were observed by Brusich et al . ( 48 ), who found that gram-negative bacteria were the leading causative agents (82.03%) of VAP and were even multidrug-resistant. Thus, we must also consider fungi, especially in immunocompromised patients ( 49 ).…”
Section: Discussionmentioning
confidence: 99%
“…Similar findings were observed by Brusich et al . ( 48 ), who found that gram-negative bacteria were the leading causative agents (82.03%) of VAP and were even multidrug-resistant. Thus, we must also consider fungi, especially in immunocompromised patients ( 49 ).…”
Section: Discussionmentioning
confidence: 99%